Cloning of a functional 25‐hydroxyvitamin D‐1α‐hydroxylase in zebrafish (Danio rerio). (7th October 2014) - Chun, Rene F.; Blatter, Elizabeth; Elliott, Stephanie; Fitz‐Gibbon, Sorel; Rieger, Sandra; Sagasti, Alvaro; Adams, John S.; Hewison, Martin
<x xml:space="preserve">Abstract</x> Activation of precursor 25‐hydroxyvitamin D3 (25D) to hormonal 1, 25‐dihydroxyvitamin D3 (1, 25D) is a pivotal step in vitamin D physiology, catalysed by the enzyme 25‐hydroxyvitamin D‐1α‐hydroxylase (1α‐hydroxylase). To establish new models for assessing the physiological importance of the 1α‐hydroxylase‐25D‐axis, we used Danio rerio (zebrafish) to characterize expression and biological activity of the gene for 1α‐hydroxylase (cyp27b1). Treatment of day 5 zebrafish larvae with inactive 25D (5–150 nM) or active 1, 25D (0.1–10 nM) induced dose responsive expression (15–95‐fold) of the vitamin D‐target gene cyp24a1 relative to larvae treated with vehicle, suggesting the presence of Cyp27b1 activity. A full‐length zebrafish cyp27b1 cDNA was then generated using RACE and RT‐PCR methods. Sequencing of the resulting clone revealed an open reading frame encoding a protein of 505 amino acids with 54% identity to human CYP27B1. Transfection of a cyp27b1 expression vector into HKC‐8, a human kidney proximal tubular epithelial cell line, enhanced intracrine metabolism of 25D to 1, 25D resulting in greater than twofold induction of CYP24A1 mRNA expression and a 25‐fold increase in 1, 25D production compared to empty vector. These data indicate that we have cloned a functional zebrafish CYP27B1, representing a phylogenetically distant branch from mammals of this key enzyme in vitamin D metabolism. Further analysis of cyp27b1 expression and activity in zebrafish may provide new perspectives on the biological importance of 25D metabolism. Copyright © 2014 John Wiley & Sons, Ltd.